Family health multiprofessional residency and the education of psychologists to work in basic care - Clemente, Anselmo; Matos, Damaris Roma; Grejanin, Danitielle K. Marques; Santos, Heloísa Elaine dos; Quevedo, Michele Peixoto; Massa, Paula Andrea (Saúde e Sociedade, 2008)
The Family Health Program (FHP) emerged in Brazil as a strategy of basic health care reorientation. The incorporation of Mental Health professionals in the FHP was not included in Directive 648 (year?), which defines minimum resources for the teams' work. In 2007, the Brazilian Ministry of Health approved the Family Healthcare Nuclei. The Multiprofessional Family Health Residency was a proposal that was coordinated by the Santa Marcelina Faculty and Hospital. It had ten professional categories, one of them being the psychologists. This work aims to reflect on and analyze the resident psychologists' practice and contribute to the discussion about the possibilities for the psychologists' work in the FHP in the city of São Paulo. It is a descriptive research; more specifically, a case study. The objective is the systematization of the practices, of the process of construction of the monthly production table and of some data it provides. The results are: categories description, the monthly production table, with some adaptations based on the codes of the Day-Care Information System that were attributed to psychologists, and a framework with quantitative data. It was possible to notice that: FHP principles, having attended a psychology undergraduation course and being part of the residency program are related with the psychologists' own history. The conclusion is that, although quantifying is necessary for the understanding of the practices, it is not sufficient to assess the complexity, efficacy and effectiveness of the practices. In addition, quantifying does not reveal the extent to which the Day-Care Information System is not prepared to register, control and inspect the psychologists who work in the FHP.